Portraying the Students’ Perception on English Speaking Class Activities within Independent Curriculum Implementation: A Photovoice Study - Puteri, Siti Azizah; Asfihana, Raida (Institut Agama Islam Negeri Madura, 2024)
Abstract: This research aims to explore the senior high school students’ perception on Independent Curriculum implementation in English as a Foreign Language (EFL) classroom, particularly in English-speaking class activities. The shift from the previous curriculum to the independent curriculum resulted in many significant changes for teachers and students. In this case, the English subject experienced a complete change when the independent curriculum was implemented in schools, especially in teaching speaking skill. Using Photovoice research design, the researchers observed the speaking class, analyzed the photos taken by eleven students from three different classes during English-speaking activities and administered in-depth interview to these participants dealing with their photos. This research was conducted at SMAIT Ukhuwah Banjarmasin, South Kalimantan. The findings portrayed that the photos taken by students in the English-speaking class captured memorable, harmonious learning moments that were conducive, communicative, informative, and an accurate depiction of the atmosphere of the English-speaking class. This is further demonstrated from the students’ perspective through their photos showing communicative activities during English-speaking classes since the photos portray a well-organized, positive, engaging, and fun classroom environment as well as emphasizing individual development in line with the independent curriculum demand. The research highlights the effectiveness of the Independent Curriculum in fostering student engagement and communicative activities, suggesting that visual-based methodologies like Photovoice can provide meaningful insights into classroom dynamics